Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Prediksi Financial Distress - Aline Zelika; M Hendri Yan Nyale (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze publicly listed Indonesian firms' financial health in 2020 and 2022 in terms of profitability, liquidity, and leverage. A quantitative method is used to describe the numerical data in this investigation. Using a purposive sample technique, this research uses financial reports of BUMN Go Public firms traded on the IDX between 2020 and 2022 as secondary data. The data acquired is 64 data points, as 16 firms may match the criterion. This study's findings show that liquidity (CR) significantly affects financial distress, but profitability (ROA) and leverage (DER) only marginally do so. Keywords: Profitability, Liquidity, Leverage, Financial Distress.